Improvement of dynamic properties of automatic control systems by means of deadbeat feedback - Dyussembekova, A.S.; Ismailov, Zh.T.; Kubayeva, U.S. (Publishing House of the KarSU named after E.A.Buketov, 2015)
The use of deadbeat feedback for improvement of dynamic properties of automatic control systems is considered. In this work the following mechanism is described, for work stabilization of which, the principle of coverage is used by negative feedback. Improvement of dynamic characteristicsof the following mechanism by introduction of deadbeatfeedback is considered. The parameters of deadbeatfeedback promoting that the studied system worked with in advance set error are determined. The description and characteristics automatic control systemswith deadbeat feedback are given, the formulas defining living conditions of fluctuations are developed and operational characteristics are given.
Keywords: automatic control; feedback; the following mechanism; stability; deadbeatfeedback; dynamic characteristics